(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
It is believed that current testing procedures in the wave energy sector are not well-balanced. Most laboratory testing has been focused on functional tests (e.g. of proof of concept and performance assessment for example) disregarding other key performance measures such as reliability and survivability. A new testing procedure that reduces development time and cost, while enabling better understanding of reliability and survivability of critical components at early Technology Readiness Levels (TRLs) has been proposed within the VALID project. In the context of VALID, the work in this paper relates reliability of the critical component to the cost of the whole system, i.e. the wave energy converter. There is usually a trade-off between a very reliable component (low maintenance and high unit cost) against a component with a lower lifetime, lower unit cost and higher maintenance. The loss of revenue of a component failing more time during the project lifetime shall be evaluated against different maintenance strategies and the capital expenditures of the overall system and the component of focus. For that, the LCOE or Levelised Cost of Electricity seems to be the parameter more relevant to capture all these variations. A sensitivity analysis will consider how varying failure rates, component’s cost and maintenance costs affect CAPEX, OPEX and accumulated energy production along project’s lifetime. The assessment will focus on selected critical components representative of three wave energy technologies: CorPower, IDOM and Wavepiston. The three user cases of the VALID project will guide the work, though it is the aim that results will be applicable beyond the VALID project. Initially, a relative quantification of the impact on the LCOE of increasing the performance and reliability of the critical component will be done. As output data comes from the experimental results, this quantification will be refined. VALID is a Horizon 2020 research project where fourteen partners around Europe are collaborating into developing a new hybrid testing platform and methodology for critical components. VALID aims at integrating both reliability and testing methods together with relevant data on component failures early in the design and testing process to ensure that the proposed testing procedure is built upon past experience. The focus of the present paper is to statistically relate the realibility of the critical component to the costs of whole system.